Ação formativa e aprendizagem: tecendo novas possibilidades para as práticas pedagógicas - Souza, Clarissa Medianeira Caxambú da Rosa de (2019)
This dissertation is connected to the Center of Studies and Research about Schooling and Inclusion (NUEPEI in the original language) and to the Post Graduation Program in Public Policies, at the Federal University of Santa Maria (UFSM), Research line 2 – Pedagogical Management and Educational Context. The research problem is to understand how the in-service teacher training can constitute a strategy to reflect on the learning conceptions and their effects in the pedagogical practices. In terms of methodology, the research presents a qualitative approach, through a critical-collaborative action research from Pimenta (2005), Jesus (2008), Tripp (2005) and it relies on the possibilities of sensitive hearing based on Barbier (2004). The investigation emerges in the scholar context having as partners the teachers from an elementary school – city’s municipal education system in Santa Maria/RS, and the data production happened with the analysis of the school document registrations, with narratives of teachers and with the data analysis produced during the formative process, registered in a journal, aiming at identifying in the in-service teacher training a process to reflect learning conceptions and the qualification of pedagogical practices in order to minimize the difficulties for the learning process. The theoretical foundations which support this research concentrate on three big areas: Learning, using authors such as Maturana (1982; 1996; 2001; 2002), Maturana and Varela (2001), Masschelein and Simons (2017), Pellanda (2009); Pedgogical Practices, using authors like Meirieu (1998; 2002), Vieira (2013) and Teacher Training, from the perspective of Tardif (2014). The research considered two main analytical routes, one focused on the learning conceptions and the reflections on the pedagogical practices, based on Maturana and Varela (2001) and Meirieu (1998; 2002). The second analysis was centered on the teaching knowledge and on the experiences of the formative process, based on Tardif (2014), Bridi Filho and Bridi (2016) and Cosenza and Guerra (2011). As main results, it is evident that the group of teachers who participated in the research shares a learning conception, based on the interaction between the environment and the individuals involved in the learning process. They understand the knowledge as a continuous phenomenon throughout life, which takes up a liberating dimension of the individual. It was possible to observe that the posture and the way how the professor deals with the educational project is strongly connected to his living/knowing the world. It is essential to underline the relevance of building a space in the context of teaching practice, directed to continuous training, in which the teacher can think, reflect and problematize the everyday challenges, through a diversity of methodologies. Besides that, the movements of this research reverberated in the product proposal of formative action in service, called “Triangle of Formative Process”, which aims at helping the qualification of pedagogical practices in the scholar context.